State Contributory Pension reform: Winners and losers. Evidence from the Irish Longitudinal Study of Ageing - Theano Kakoulidou; Claire Keane; Simona Sándorová (The Economic and Social Research Institute (ESRI), 2024)
The Yearly Average Method used in calculating State Contributory Pension entitlements has been criticised for creating anomalies, particularly for women. It has been announced that from 2034 onwards, entitlements will be based fully on the new Total Contributions Approach. This paper examines the impact of this move, examining who will gain or lose from this change. Overall, we find little change in the average weekly pension rate with a slight fall for men and no change for women. These average changes mask gains and losses for some; around 14 per cent of women and 12 per cent of men will face a loss under the Total Contributions Approach while 5 per cent of men and 30 per cent of women will see a gain. More women will qualify for the maximum pension rate under the Total Contributions Approach due to the removal of anomalies associated with the Yearly Average Method. On average, losses are very small, less than 1 per cent of pension income, but will be largest at the bottom end of the income distribution.
Keywords: 330